THE RELATIONSHIP BETWEEN SCHOOL DISCIPLINE AND STUDENT ACHIEVEMENT - Najbiddinova Farangiz Zarif qizi (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
School discipline is an essential factor affecting student academic achievement and the overall effectiveness of the educational environment. This article examines the relationship between school discipline and student performance, focusing on how structured rules, effective classroom management, and positive teacher–student relationships contribute to academic success. The paper also addresses the negative effects of poor discipline, including reduced student engagement and lower academic results. Particular attention is given to modern approaches that emphasize positive discipline, mutual respect, and the development of student self-discipline. The role of teachers and parents in maintaining a supportive and well-organized learning environment is also discussed. The study concludes that effective discipline systems play a significant role in improving both academic results and students’ personal development, making discipline a key component of educational success.